Optimasi Kombinasi Asam Stearat dan Trietanolamin dalam Formula Krim Ekstrak Daun Legetan (Spilanthes acmella L.) sebagai Antioksidan secara Simplex Lattice Design - Astiti Noer Cahyati; Dewi Ekowati; Reslely Harjanti (Jurnal Farmasi Indonesia, 2015)
Legetan leaves extract has been shown to have antioxidant activity because it contains flavonoids and polyphenols. The use of legetan leaves extract directly assessed less well, so that it made cream preparations to make it more convenient to use. This study aimed to obtain the optimum formula of cream of legetan leaves extract using additional materials stearic acid and triethanolamine by Simplex Lattice Design method. The legetan leaves extract obtained by maceration using ethanol 96% solvent was then evaporated to obtain a viscous extract. Legetan leaves extract cream were made three formulas based on the Simplex Lattice Design. Cream were tested physical properties include organoleptic test, viscosity, viscosity shift, dispersive power, pH, and antioxidant activity. Optimum formulation parameters based on physical properties, namely: viscosity, viscosity shift, dispersive power, using Design Expert software version 8.0.6.1. Optimum formula was made and the physical properties of the cream was analyzed using t-test. Antioxidant activity was tested by DPPH methode. Optimum formula cream of legetan leaves extract obtained from composition stearic acid 1,824% and triethanolamine 2,176% with the physical properties of the response of the optimum formula predictions and experimental results showed no significant difference. Cream optimum was 10% extract with antioxidant activity of 443,232 ppm after two day and 1233,3 ppm after one month.